2021
DOI: 10.3390/ani11072037
|View full text |Cite
|
Sign up to set email alerts
|

Response of Reeves’s Pheasants Distribution to Human Infrastructure in the Dabie Mountains over the Last 20 Years

Abstract: Human infrastructure development drives habitat loss and fragmentation worldwide. In China, over the last 20 years, rapid infrastructure development impacted the habitats of endangered species. To facilitate conservation efforts, studies of how human infrastructure affects the distribution of Reeves’s pheasant (Syrmaticus reevesii), an endangered species by the International Union for Conservation of Nature (IUCN) and a nationally protected species in China, are critically needed. We assessed how the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Over the last 20 years, rapid infrastructure development in China has had a severe impact on the habitats of endangered species, since the distance from their core habitat to the impervious infrastructure is shortening every year [16]. The response curves for both blood pheasants and blue eared pheasants indicated that the major sustainable habitats of the two pheasants fell within 10 km of transportation infrastructure (i.e., distance to roads) and built-up areas (i.e., distance to buildings) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 20 years, rapid infrastructure development in China has had a severe impact on the habitats of endangered species, since the distance from their core habitat to the impervious infrastructure is shortening every year [16]. The response curves for both blood pheasants and blue eared pheasants indicated that the major sustainable habitats of the two pheasants fell within 10 km of transportation infrastructure (i.e., distance to roads) and built-up areas (i.e., distance to buildings) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Many avian species have suffered from human activities, as man-made infrastructure have cut through and fragmented their habitat [16]. Gallinaceous birds, which are grounddwelling with limited disperse ability [5,[17][18][19], are particularly vulnerable to human overexploiting and infrastructure expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The study site was located in Pingjingguan village, Guangshui City, Hubei Province, China (113 [31]. The land use types include coniferous forest, deciduous broad-leaved forest, coniferous broad-leaved mixed forest, undergrowth, wasteland, water sources, and human-modified habitat, such as farmland, forest paths, and residential and paved roads.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%